Voluntary community service in medical school: a qualitative study on obstacles faced by student leaders and potential solutions - Alvona Zi Hui Loh; Julia Shi Yu Tan; Jeannette Jen-Mai Lee; Gerald Choon-Huat Koh (Taylor & Francis Group, 2015)
Purpose: In medical school, students may participate in various community involvement projects (CIP), which serve disadvantaged communities. However, several obstacles may arise during these projects. The authors conducted a qualitative study with the primary aim of understanding the obstacles and corresponding potential solutions when medical students in Singapore participate in local CIP (LCIP) and overseas CIP (OCIP). Design: The authors recruited medical students from Yong Loo Lin School of Medicine, National University of Singapore, who were also leaders of a specific community service project done in medical school. Twelve one-to-one interviews were held for the participants from 6 to 8 January 2013. Participants were led in a discussion based on an interview guide. The interviews were audio-recorded and transcribed into free-flow text. Subsequently, content and thematic analyses of the transcripts were performed independently by three researchers. Results: The medical students faced many common obstacles during their community service projects. These obstacles include difficulties in recruiting and managing volunteers, attaining recognition or credibility for the project to acquire funding and resources, adjusting to a different culture or language, setting goals, and facing project-specific obstacles. Potential solutions were offered for some obstacles, such as building a strong executive committee for the project, grooming successive batches of leaders, and improving the project's public image, mentorship, reflections, and sustainability plans. Conclusions: Mentorship, reflections, and sustainability are potential solutions that have been proposed to tackle the obstacles faced during community service participation in medical school. However, there may still be difficulty in solving some of the problems even after these measures are put into practice. Future research may focus on evaluating the effectiveness of these suggested solutions.